Answer:
The inverse of
is ![y=\sqrt{(4x+28)}+2](https://tex.z-dn.net/?f=y%3D%5Csqrt%7B%284x%2B28%29%7D%2B2)
Step-by-step explanation:
Given equation :![2(x - 2)^2 = 8(7 + y)](https://tex.z-dn.net/?f=2%28x%20-%202%29%5E2%20%3D%208%287%20%2B%20y%29)
![\Rightarrow \frac{2(x-2)^2}{8}=7+y\\\Rightarrow \frac{2(x-2)^2}{8}-7=y](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cfrac%7B2%28x-2%29%5E2%7D%7B8%7D%3D7%2By%5C%5C%5CRightarrow%20%5Cfrac%7B2%28x-2%29%5E2%7D%7B8%7D-7%3Dy)
Replace x with y and y with x
So, ![\Rightarrow \frac{2(y-2)^2}{8}-7=x\\\Rightarrow \frac{2(y-2)^2}{8}=x+7\\\Rightarrow 2(y-2)^2=8(x+7)\\\Rightarrow (y-2)^2=4(x+7)\\\Rightarrow (y-2)=\sqrt{4(x+7)}\\\Rightarrow y=\sqrt{4(x+7)}+2\\\Rightarrow y=\sqrt{4x+28)}+2](https://tex.z-dn.net/?f=%5CRightarrow%20%5Cfrac%7B2%28y-2%29%5E2%7D%7B8%7D-7%3Dx%5C%5C%5CRightarrow%20%5Cfrac%7B2%28y-2%29%5E2%7D%7B8%7D%3Dx%2B7%5C%5C%5CRightarrow%202%28y-2%29%5E2%3D8%28x%2B7%29%5C%5C%5CRightarrow%20%28y-2%29%5E2%3D4%28x%2B7%29%5C%5C%5CRightarrow%20%28y-2%29%3D%5Csqrt%7B4%28x%2B7%29%7D%5C%5C%5CRightarrow%20y%3D%5Csqrt%7B4%28x%2B7%29%7D%2B2%5C%5C%5CRightarrow%20y%3D%5Csqrt%7B4x%2B28%29%7D%2B2)
So, Option C is correct
Hence The inverse of
is ![y=\sqrt{(4x+28)}+2](https://tex.z-dn.net/?f=y%3D%5Csqrt%7B%284x%2B28%29%7D%2B2)
Answer:
m - 8/3
Step-by-step explanation:
Find the slope of the line between (-3,1) and (6,7) using m = (y2 - y1) / (x2-x1)
which is the change of "y" over the change of "x"
m = (7 - (-1) / 6 - (3)
m = 8/3
The answer is should be C cause i took a test on it like 2 weeks ago .